SOVEREIGNTY IN THE CYBERSPACE: CONTESTATION OF CONCEPTS AND POLICIES - Chin, Yik Chan; Li, Ke (AoIR Selected Papers of Internet Research, 2021)
In recent years, various claims of cyberspace sovereignty, including 'data sovereignty', 'digital sovereignty' and 'technological sovereignty', have attracted widespread attention. In this research, we examine the various academic positions and governments’ policies on different "sovereignty" concepts in cyberspace, and to explore the controversies, evolution and future development of these concepts. Research questions are: 1) what are the definitions of the academic community on these concepts including ‘cyber’, 'digital', 'data' and 'technology’ sovereignty ; 2) what are the positions and claims of major governments on these sovereignties; and 3) what are the overlaps, differences and conflicts between those positions and the underlying reasons? Methodologically, this paper will use a historical documentary analysis approach. The types of documents used include two categories: (1) Primary sources: Initiatives, laws, regulations, drafts, ordinances and strategic proposals issued by governments on sovereignty in cyberspace; 2) secondary source: academic literatures related to various concepts of sovereignty in cyberspace, including journal papers, academic conference reports and books. In this paper, government policy documents from China, the EU and the US for the period 2010-2021 will be chosen as the main subjects of study. There has been a major conceptual and position differences among these countries/region on the "sovereignty " in cyberspace, they represent the focus of the debates.